Teaching spatial planning as a tool in project management for public infrastructure - Barrantes-Chaves, Karla (2023)
Spatial planning seeks to organise land uses within a territory sustainably, trying to minimise conflicts between them. By its nature, it is an interdisciplinary field related not only to physical aspects of the territory but also to public policies, citizen participation and institutional regulations. Furthermore, the efficient organisation of the city facilitates public infrastructure management and reduces bureaucratic processes. This paper aims to present an experience of eight years of teaching planning for the Topographic Engineering degree at the University of Costa Rica; it explores experiences using different didactic techniques. Methodologically, this work is based on assessments of teaching performance from 2010 to 2021 (with a four-years gap), from a course focused on planning; these appraisals were carried out every six months and were completed by students anonymously. This information is complemented by the experiences of university lecturers who have included aspects related to planning in their modules. Finally, through qualitative analysis, this paper aims to show didactic strategies that have been best adapted to the learning objectives from the modules, as well as to make visible the importance of teaching planning to speed up the processes of public investment in the city. Among the main findings are the effectiveness of field visits, the use of Geographic Information Systems in the classroom and the use of collaborative tools in teaching territorial issues in engineering.